Preparation of Silver Nanoparticles from Silver(I) Carboxylate: Multicrystallity and Mechanisms - Piao, Longhai; Park, Cheol-Hee; Yoon, Sungho (Asian Journal of Chemistry, 2011)
The properties of nanomaerials can be differentiated significantly by controlling the crystallinity of the nanoparticles along with their sizes and shapes. The silver nanoparticles prepared from the decomposition of silver carboxylate reported to have multi-crystallinity even though their diameters were extremely small. This paper provides more detailed transmission electron microscopy and X-ray diffraction evidences for the 100 % existence of multi-crystalline silver nanoparticles, prepared from a facile one-pot organic phase synthesis and proposes a detailed silver nanoparticle growth mechanism based on these results.